Role of some biofertilizers and antioxidants on onion white rot disease and yield production - Saleh, Wagida A. M. (2008)
Single and combined applications of two biofertilizers and/or two antioxidants to Giza 6 onion cultivar seedlings just before transplanting in artificially infested soil with Sclerotium cepivorum reduced white rot disease incidence, (01) than control. The best significant disease reduction was observed when Biogien, Microbien and Tartaric acid were applied together (6.7% 01). Microbien + Amonium.tartrate application reduced (01) to be 13.3% and this was 20% when Biogien + Tartaric acid treatment was used. Under field and natural inoculation conditions in Malawi, Minia governorate at 2005 and 2006 seasons; the applications of biofertilizers and/or antioxidants significantly reduced white rot (w.r.) disease incidence and increased onion bulb yield. Microbien was superior in reducing the disease followed by Amonlum tartrate and Biogien + Amonium tratrate. There was a big correlation between (w.r.) disease reduction and increasing onion yield production. Total phenols were generally increased than control (n response to biofertilizers and/or antioxidants application to Giza 6 onion cultivar plants. However, application of B(ogien + Microbien + Amonium tartrate gave the highest estimated phenolic compounds. Free phenols were severly lesser than conjugated phenols. Polyphenol oxidase activity in onion plants was lesser than contro( ones in response to the applications of any biofertilizer and/or antioxidant. White peroxidase activity was higher than control in all cases except Amonium tartrate treatment.
Includes references.
Summary in Arabic.
1
Keywords: White rot (Onions).; Onions -- Diseases and pests -- Control; Onions -- Fertilizers; Onions -- Yields; Biofertilizers; Antioxidants -- Research